Health care administration and drug policy. (20th February 2023) - Duncan, David F.; Ellis‐Griffith, Gregory; Nicholson, Thomas; Nimkar, Swateja
Abstract: The American healthcare system faces a potential reorganization of the way in which services are provided and financed. We argue that healthcare administrators need to be increasingly aware of the ways in which our nation's illicit drug policy, commonly referred to as the 'War on Drugs', affects the provision of health services. A large and growing portion of the US population uses one or more of the currently illegal drugs and some of these persons suffer from an addiction or other substance use disorder. This is clearly demonstrated by the current opioid epidemic which is not yet being adequately controlled. Providing specialty treatment for drug abuse disorders will be increasingly important for healthcare administrators thanks to recent mental health parity legislation. At the same time, drug users and abusers will be increasingly encountered while providing care not specifically tied to drug use or abuse. The character of our current national drug policy has an important impact on how drug abuse disorders are treated and how the health delivery system responds to drug users who are increasingly often encountered in primary care, emergency care, specialty care, and long‐term care settings. Highlights: The war on drugs is regularly omitted in health in discussions of healthcare management and policy. Issues range from careful management of controlled substances, defined by the World Health Organisation, as they relate to patients and staff within a facility or programme. The uses range from the micro as noted in the bullet above, to the macro issues of integration with the community and population in which the faculty is located. The need for education enhancements for all staff.